The Pre-Transplant Drop in Panel-Reactive Antibodies Titer Evaluated Using Complement-Dependent Cytotoxicity (PRA-CDC) and the Risk of Early Acute Rejection in Sensitized Kidney Transplant Recipients - Aureliusz Kolonko; Beata Bzoma; Piotr Giza; Beata Styrc; Michał Sobolewski; Jerzy Chudek; Alicja Dębska-Ślizień; Andrzej Więcek (Medicina, 2018)
Background: The panel-reactive antibodies that use the complement-dependent cytotoxicity test (PRA-CDC) are still a standard method for monitoring the degree of immunization in kidney transplant candidates on active waiting lists in some countries, including Poland. The aim of this study was to analyze the relationship between the maximum and the last pre-transplant PRA titer on the percentage of positive cross-matches and rate of early acute rejection episodes. Material and methods: The retrospective analysis included 528 patients from two transplant centers. All patients were divided into three groups, depending on their peak and last pre-transplant PRA titers. There were 437 (82.8%) patients with peak PRA <20% (non-sensitized group, non-ST) and 91 (17.2%) patients with peak PRA >20%. Among the latter group, 38 had maintained PRA level >20% at the time of transplantation (sensitized patients, ST), whereas 53 had pre-transplant PRA ≤20% (previously sensitized patients, prev-ST). Results: The percentages of positive crossmatches were 76.9% in ST and 53.7% in prev-ST groups versus 18.4 in non-ST group (both p < 0.001). The acute rejection rates were 18.9, 17.6 and 6.8%, respectively (p < 0.001 for ST or prev-ST versus non-ST). The pre-transplant PRA titer drop did not decrease the risk of early acute rejection [OR = 1.09 (95% CI: 0.31–3.85)] in a multiple logistic regression analysis. The occurrences of primary graft non-function and delayed graft function were similar in all study groups. Conclusions: Previously immunized kidney transplant candidates even with substantial decrease in pre-transplant PRA-CDC levels are still at high immunological risk when compared with non-immunized patients, and they should receive lymphocyte-depleting induction therapy.